1988
DOI: 10.1063/1.455065
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and stabilities of small silicon clusters: A theoretical study of Si7–Si1

Abstract: A b initio calculations have been performed to study the structures and energies of intermediate-sized silicon clusters (Sin, n=7–10). All geometries have been optimized at the Hartree–Fock (HF) level of theory with the polarized 6-31G* basis set. The harmonic vibrational frequencies have been evaluated at the HF/6-31G* level of theory. Electron correlation effects have been included by means of fourth order Mo/ller–Plesset perturbation theory. The most stable structure for Si7 is a pentagonal bipyramid and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
180
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(210 citation statements)
references
References 56 publications
30
180
0
Order By: Relevance
“…In this case cages are predicted for upwards of 4 atom clusters. The 6 and 7 atom structures predicted are in agreement with recent experimental results [25,26]. An interesting atom structures are predicted to have a lower energy with this parameterisation.…”
Section: ¡ ©supporting
confidence: 80%
“…In this case cages are predicted for upwards of 4 atom clusters. The 6 and 7 atom structures predicted are in agreement with recent experimental results [25,26]. An interesting atom structures are predicted to have a lower energy with this parameterisation.…”
Section: ¡ ©supporting
confidence: 80%
“…This is because the bonding feature of the Si 5n H 10 (n is an integer) clusters is very similar to that of the infinite SWSNTs; namely, the coordination number of every Si atom (except those at the ends) is fourfold. Note that previous ab initio calculations have shown that small-sized silicon clusters tend to favor a higher coordination number than fourfold (22)(23)(24). Hence, without the hydrogen termination at the ends, the stacked-pentagon silicon clusters will be unstable.…”
mentioning
confidence: 98%
“…The true equilibrium state under all of these conditions is nearly complete conversion of silane to crystalline silicon and molecular hydrogen. Equilibrium calculations that included pure silicon clusters Si n (1 e n e 10), using the same thermochemistry discussed in previous work, 34,52,57 predicted that the Si 7 cluster would be the dominant cluster present at partial equilibrium among the pure silicon clusters and the species shown in Figure 2. However, in the kinetic simulations presented below, formation of pure silicon clusters was found to be unimportant compared to formation of hydrogenated silicon clusters.…”
Section: Thermochemistry Of the Silicon Hydridesmentioning
confidence: 99%